Estimation of basic reproduction number (R0) of African swine fever (ASF) in mid-size commercial pig farms in Vietnam - Mai, Nguyen Tuan Anh; Trinh, Thi Bich Ngoc; Nguyen, Van Tam; Lai, Thi Ngoc Ha; Le, Nam Phuong; Nguyen, Thi Thu Huyen; Nguyen, Thi Lan; Ambagala, Aruna; Do, Duc Luc; Le, Van Phan (Frontiers in Veterinary Science, 2022)
African swine fever (ASF) is a devastating disease affecting the global swine industry. Recently it has been spread to many countries in Africa, Europe, Asia, and the Caribbean, leaving severe damage to local, regional, national, and global economies. Due to its highly complex molecular characteristics and pathogenesis, the development of a successful vaccine has been an unmet challenge. Therefore, ASF control relies solely on biosecurity, rapid detection, and elimination. Epidemiological information obtained from natural ASF outbreaks is critical for designing and implementing of ASF control measures. Basic reproduction number (R0), an epidemiological metric used to describe the contagiousness or transmissibility of infectious agents, is an important epidemiological tool. In this study, we have calculated R0 for the in-farm spread of ASF among fattening pigs and sows in two mid-size commercial pig farms HY1 and HY2, that practiced the spot removal approach in controlling ASF outbreaks in Vietnam. The R0 values for sows and fattening pigs were 1.78 (1.35 – 2.35) and 4.76 (4.18 – 5.38) for HY1; and 1.55 (1.08 – 2.18) and 3.80 (3.33 – 4.28) for the HY2, respectively. This is the first study to evaluate the transmission potential of ASF in mid-size commercial pig farms in Vietnam. Based on the R0 values, we predict the spot removal approach could be used to successfully control ASF outbreaks in mid-size commercial sow barns but not in fattening pens.